Sequence-sorted redox-switchable hetero[3]rotaxanes. Issue 1 (16th November 2021) - Gaedke, Marius; Hupatz, Henrik; Witte, Felix; Rupf, Susanne M.; Douglas, Clara; Schröder, Hendrik V.; Fischer, Lukas; Malischewski, Moritz; Paulus, Beate; Schalley, Christoph A.
Abstract : Programming the sequence of functional units in redox-switchable hetero[3]rotaxanes is achieved by integrative self-sorting for a library of five crown ethers. Abstract : From a library of five crown ether macrocycles with different ring sizes and redox-active moieties, such as tetrathiafulvalene (TTF) and naphthalene dimiide (NDI), directional heterocircuit[3]rotaxanes were constructed. Using an axle with two binding sites with different steric accessibility, the concept of integrative self-sorting was applied to program the sequence of functional units in heteropseudo[3]rotaxanes. Depending on binding strength and ring size of the smaller macrocycles, different heteropseudo[3]rotaxane selectivities and stabilities were determined by 2D NMR spectroscopy and tandem mass spectrometry. A heteropseudo[3]rotaxane with rotaxane-like behaviour was isolated chromatographically, displaying electrochemically "frustrated" properties. A robust synthetic procedure was developed allowing the synthesis of four new hetero[3]rotaxanes incorporating specific sequences of functional units. Sequence pseudoisomeric rotaxanes which have the naphthalene diimide subunit at two different positions show distinct electrochemical properties. DFT calculations suggest that this differences could arise from a folding of the structure, in which the redox-active moieties stack with a stopper unit. This study presents a blueprint for the construction of hetero[3]rotaxanes with sequential control of the functional units along the track of the axle and paves the way to extend the functionality of mechanically interlocked molecules.